Course Crafting in the Pandemic: Examination of Students' Positive Experiences - Lakshmi Narayanan; Ramzi Nasser; Shanker Menon; Brett Wallace (MDPI AG, 2024)
College students' positive experiences were examined before and during COVID-19 when courses transitioned to a new format. During COVID-19, university courses at a state university in the US transitioned to a new online format. This study observed the affective experiences of students through the instructors' course crafting during times of crisis. The method of critical incident qualitative data collection examined what students perceived as positive experiences. Students' perceptions were examined, and the nature and types of positive experiences were examined before and during the pandemic. This comparison provided insights into the emotions and feelings experienced between the two groups (Before COVID-19 and During COVID-19). As courses were modified and redesigned for remote learning, examination of the findings showed students' positive experiences considering the faculty recrafting their courses, which gave a valuable insight into the dynamics of these positive experiences in the teaching and learning process. Educators crafted their courses' changing format and provided emotional support, empathy, kindness, reassurance, and encouragement when needed. The implications of these findings and understanding how we can thrive and flourish even in very challenging times in the virtual environment is discussed.